A novel, precipitated polybutylene terephthalate feedstock material for powder bed fusion of polymers (PBF): Material development and initial PBF processability. (1st January 2021) - Dechet, Maximilian A.; Gómez Bonilla, Juan S.; Grünewald, Moritz; Popp, Kevin; Rudloff, Johannes; Lang, Marieluise; Schmidt, Jochen
Abstract: The development of a novel polybutylene terephthalate (PBT) feedstock material for powder bed fusion of polymers with laser beam (PBF-LB/P) by means of liquid-liquid phase separation (LLPS) and precipitation is outlined. Appropriate solvents for precipitation have been identified by a screening approach based on solubility parameters. Feasible system compositions and solution and cloud point temperatures were determined. For the most promising solvent, cyclopentanone, a parameter study on the influence of stirring conditions during precipitation was performed. The obtained products were characterized with respect to their particle size distribution, particle shape, phase morphology, thermal properties and melt viscosity. Under optimized process conditions, PBT particles of high degree of crystallinity with narrow size distribution and a mean diameter of 36 μm were obtained; flowability was improved by dry coating. The initial PBF-LB/P processability was assessed by building single layers in a parameter study using a Formiga P110 machine. Dense single layers were obtained at laser power PL  = 11.5 W, scanning speed vS  = 4000 mm/s, hatch distance hS  = 0.24 mm and layer thickness dS  = 0.1 mm. Best to the authors' knowledge, this is the first study in the open literature reporting on a PBT feedstock material obtained by liquid-liquid phase separation and crystallization. Graphical abstract: Unlabelled Image Highlights: Development of PBT PBF feedstock with narrow size distribution, high roundness and circularity produced via precipitation. PBT feedstock material of good flowability, high degree of crystallinity and broad PBF processing window. Solubility parameter screening and cloud point measurement for polymer-solvent system and process condition identification. Thorough characterization of developed PBT feedstock powder with respect to thermal, rheological and bulk solid properties. Derivation of PBF process parameters for the precipitated PBF feedstock via parameter study on a commercial PBF machine.